(untitled) (Libellarium: journal for research in the field of information and related sciences, 2024)
Purpose. The aim of this paper is to explore and highlight the significance of book covers, particularly those illustrated by Edo Murtić, in terms of their cultural, historical, and aesthetic value. The focus is placed on the covers preserved in the Bjelovariana Local Collection of the “Petar Preradović” Public Library and their contribution to the preservation of local and national cultural heritage. Methodology. The paper employs an analytical approach, comparing examples of book covers in the online catalogues of four libraries, with special emphasis on the covers illustrated by Edo Murtić. The methodology includes a literature review and the analysis of selected examples from the Bjelovariana Local Collection. Social implications. Book covers play an important role in cultural heritage as they reflect social, economic, and technological changes throughout history. Their preservation in library collections, especially local ones, provides a deeper insight into the evolution of artistic trends and cultural norms, thus contributing to the preservation of community identity and historical memory. Originality. The subject of book covers in the context of their historical and aesthetic significance has not yet been systematically approached in Croatian professional literature. This paper offers the first comprehensive overview of Murtić’s book covers, underscoring the importance of their bibliographic documentation, collection, and preservation within library collections.